Errors In Spoken Production Made By Accounting Department Students In English Tutorial Program (ETP) Of Muhammadiyah University Of Surakarta - Karismawati, Nunung, Prof. Endang Fauziati, M.Hum (2017)
This article is aimed to present the type, frequency, and dominant speech errors, and sources made by students of Accounting Department in the English Tutorials Program at Muhammadiyah University of Surakarta. The type of this research is descriptive qualitative research. The subjects are the first semester students of accounting department in English Tutorial Program (ETP). The techniques for collecting the data include: collecting the videos from tutor ETP, making the script of utterances, reading, and listening the recorded videos the utterances, and identifying and explaining. To analyze the types of errors, the writer uses theory of Clark and Clark (1972) and theory from Dulay, Burt, Krashen and Richard (1982). In the finding, researcher found speech error: (1) silent pause (19,65%), (2) filled pause (28,07%), (3) repeats (22,46%), (4) stutters (6,32%) , (5) correction (5,96%), and (6) interjection (1,40%). Morphological errors included vocabularies error (the used of Indonesian Language) (3,15%) , and error in word selection (3,16%). Syntactical errors included omission of bound morpheme [-s] as plural marker (5,26%) , of omission of preposition (2,10%), omission of to be as predicative (1,75%), and addiction of preposition (0,35%). The dominant error is filled pause. The sources of error made by students are: (1) cognitive reason and (2) psychological reason.